Coach-assessed skill learning progress of youth soccer players correlates with earlier childhood practice in other sports - Güllich, A.; Cronauer, R.; Diehl, J.; Gard, L.; Miller, C. (International Journal of Sports Science & Coaching, 2020)
The hypothesis that sport-specific skill learning is correlated with earlier childhood multi-sport practice experiences was empirically studied among youth soccer players. Fourteen youth soccer coaches (38.1 ± 12.0 years) evaluated 100 youth players (11.8 ± 0.7 years) regarding their progress in soccer-specific skill learning through the course of a one-year season. The players completed a questionnaire recording their earlier and current participation in coach-led practice and youth-led play in soccer and in other sports. Reliability of the coach rating and of players` reported sport activities ranged 0.83 = rtt = 1.00. Analyses revealed that the progress of the youth players in soccer-specific skill learning was not significantly correlated with their earlier or current amounts of coach-led soccer practice (-0.07 = rs = 0.07), youth-led soccer play (0.01 = rs = 0.08), or youth-led play in other sports (0.13 = rs = 0.22). Progress in soccer-specific skill learning was significantly correlated with the accumulated years and hours of earlier (but not current) coach-led practice in other sports (0.54 = rs = 0.57). A binary logistic regression accurately classified 83% of players with better and poorer learning progress based on earlier years and hours of practice in other sports. The observations suggest that earlier practice experiences in other sports had a lagged effect in interaction with later soccer practice and facilitated skill learning in soccer-specific practice.